Investigating the fiscal motive of state incentives for innovative and investment activity - Yereshko, Julia (Technology audit and production reserves, 2021)
The object of research is the state as an economic agent of innovative development. The analysis of scientific achievements on the issue of the state innovation and investment activity stimulation and the study of the state from the standpoint of the innovative development subject forms a fairly clear idea about the mechanisms of activation of them both, at the same time, the motives for the state to stimulate innovation remain not fully covered. The state itself is not interested in stimulating the innovation and investment processes and in transition to sustainable development. This interest is mediated, as for any other economic agent, by imbalance and/or obtaining additional economic effect in the form, for example, budget expenditures reduction; tax revenues growth, managerial staff optimization, etc. And, crucialness of purely liberal nature of any controlled influence on the system mediates that state regulatory activity should be based on the economic benefit of the agent, as opposed to the political motives of nominal adherence to the generally accepted course of development. Well-known trajectories and patterns of administrative and economic activity of the state give grounds to assume the following main economic motives for stimulating the innovation process: – increase in tax revenues (fiscal motive); – reducing the burden on the budget; – GDP growth; – increasing the country’s competitiveness; – optimization of administrative costs and management staff; – attracting program financing and investments. Prominent among which is the increase in tax revenues or fiscal motive. It can result in several areas: – from the standpoint of additional taxes due to the increase in effectiveness of legal entities innovative activity – the expansion of business activities; types and volumes of sales of products and services; increase in the number of enterprises; increase in the cost of sold products; profitability, etc.; – from the standpoint of additional taxes due to better development of the workforce – higher employment; higher wages, etc.